APLIKASI TEORI UTILITAS UNTUK MELIHAT MINAT PEMBELIAN PRODUK ASURANSI PENDIDIKAN - Desi Pangestuti, Clara (2014)
Utility is preference or value in use for taking decision by considering the risk factor using numbers representing the actual pay off value based on the decision. Utility value used for depicting the alternatives chosen by the decision maker. High utility value represents the most favorable alternative, while low utility value represents the least favorable alternative (Supranto: 374). By using utility, the interest in Manjahlega Subdistrict, Bandung City can be revealed. The issue studied in this research is about the interest of purchasing education insurance product in Manjahlega Subdistrict, Bandung City. The factor influencing interest is product policy. The sample involved in this research was 81 respondents. Data collection technique used was questionnaire distribution. The instrument used was Likert scale. Data analysis technique employed in this research was utility theory. The result of the research showed that the interest of purchasing education insurance product in Manjahlega Subdistrict, Bandung City was high. It was proven by the utility expected value which was 0.5092 for high interest, and 0.0865 for neutral.